CBIO-08. ASTROCYTE SENESCENCE CONTRIBUTES TO SEX DIFFERENCES IN GLIOBLASTOMA INCIDENCE AND OUTCOME. (9th November 2020) - Broestl, Lauren; Rhee, Gina; Grandison, Lucia; Sponagel, Jasmin; Kfoury, Najla; Hill, Cameron; Rubin, Joshua
Abstract: Sex differences in incidence and outcome are consistently observed in cancer, including in the most common malignant brain tumor – glioblastoma (GBM). Women are less likely to develop GBM and have a survival advantage compared to men. Previous research from our lab identified the proteins Rb, p16, and p21 as key mediators of female protection against cellular transformation. Strikingly, these proteins are all primary components of the senescence response, a potent cell-intrinsic anti-cancer mechanism that results in permanent cell cycle arrest, preventing proliferation of damaged cells. We hypothesized that sex differences in GBM incidence and outcome are mediated by differences in senescence induction after DNA damage in male and female cells. Using both wildtype astrocytes and a GBM model, we found that females have a lower threshold for senescence induction in response to oxidative stress, telomere shortening, and treatment with chemotherapy or radiation. Following irradiation, female GBM model cells had higher levels of p21 expression, and p21 levels correlated with the percentage of senescent cells. Knocking out p21 eliminated sex differences in the senescence response following irradiation. Achieving a better understanding of mechanisms of senescence and how they differ in male and female cells could advance development of senescence-directed therapies and potentially improve treatment for brain tumors.